A techno-economic evaluation of the geodesic dome as a possible form of low-income house in Southern Africa - Waizenegger, Philip (School of Architecture, Planning and Geomatics, 2020)
This dissertation studies the viability of one alternative building system as an option to conventional low-income housing. The need for research in this regard has been expressed by various government committees and commissions of inquiry, as well as by the private sector, to be of vital importance in facing the future housing challenge in southern Africa. The study is largely confined to black housing. The search for a form of shelter which combines traditional black low-technology and innovative Wes tern high-technology in a successful marriage, brings the geodesic dome to light. The conclusion reached is that in economic, technical and cultural terms, the dome compares favourably with conventional low-income housing. The social acceptance of the structure is a topic of research beyond the scope of this study.